Размноженне гривистого барана (Ammolragus lervia Pall.) в зоопарке «Аскания-Нова» - Лобанов, Н.В.; Треус, В.Д. (Вестник зоологии, 1971)
15 males and 8 females of Ammotragus lervia Palla s which gave 60 lambs were •delivered to the Askaniya-Nova zoo. The periods of lambing of Barbary sheep at the Zoo almost coincide with those under natural conditions (83.5% of lambings occurs in March -- May). The rut takes place in October — November, the pregnancy lasts for 155±5 days. The data are presented on the terms of sexual maturity, as well as some exterior and interior indices. An experiment of A. lervia reproduction in Askaniya-Nova testifies to the possibility of their breeding in captivity.